KORUPSI DI LEMBAGA LEGISLATIF PADA ERA OTONOMI DAERAH - R. Dyatmiko Soemodihardjo (Perspektif, 2004)
Corruption in Indonesia has been recognized in bureaucratic and banking level that nowadays it has entered the legislative level. Uncovered corruption cases on members of Province Legislative Assembly recently follows the implementation of Decree Number 22 Year 1999 that one of the aims is functioning and rolling the legislative assembly Thus it requires detail evaluation on the causes of the corruption practice in the Legislative Assembly and finally finds ways to prevent such practice.